Usability Evaluation of Electronic Health Record System around Clinical Notes Usage–An Ethnographic Study - Rizvi, Rubina F.; Marquard, Jenna L.; Hultman, Gretchen M.; Adam, Terrence J.; Harder, Kathleen A.; Melton, Genevieve B. (Applied Clinical Informatics, 2017)
Background A substantial gap exists between current Electronic Health Record (EHR) usability and potential optimal usability. One of the fundamental reasons for this discrepancy is poor incorporation of a User-Centered Design (UCD) approach during the Graphical User Interface (GUI) development process.Objective To evaluate usability strengths and weaknesses of two widely implemented EHR GUIs for critical clinical notes usage tasks.Methods Twelve Internal Medicine resident physicians interacting with one of the two EHR systems (System-1 at Location-A and System-2 at Location-B) were observed by two usability evaluators employing an ethnographic approach. User comments and observer findings were analyzed for two critical tasks: (1) clinical notes entry and (2) related information-seeking tasks. Data were analyzed from two standpoints: (1) usability references categorized by usability evaluators as positive, negative, or equivocal and (2) usability impact of each feature measured through a 7-point severity rating scale. Findings were also validated by user responses to a post observation questionnaire.Results For clinical notes entry, System-1 surpassed System-2 with more positive (26% vs. 12%) than negative (12% vs. 34%) usability references. Greatest impact features on EHR usability (severity score pertaining to each feature) for clinical notes entry were: autopopulation (6), screen options (5.5), communication (5), copy pasting (4.5), error prevention (4.5), edit ability (4), and dictation and transcription (3.5). Both systems performed equally well on information-seeking tasks and features with greatest impacts on EHR usability were navigation for notes (7) and others (e.g., looking for ancillary data; 5.5). Ethnographic observations were supported by follow-up questionnaire responses.Conclusion This study provides usability-specific insights to inform future, improved, EHR interface that is better aligned with UCD approach.
Keywords: electronic health records; interfaces; usability; graphical user interface; clinical documentation; qualitative; methodology